The relationship of gender, religious conviction and premarital sex involvement among college students in Tacloban City - Magdaraog, Ethel B.; Tupaz, Marna D. (2007)
This paper is entitled "The Relationship of Gender, Religious Conviction and Premarital Sex Involvement among College Students in Tacloban City. This study aims to know the factors that teenager to engage in premarital sex, to find out the reasons for engaging in premarital sex and to determine the relationship between gender, religious conviction and premarital sex involvement. This study used the two-way ANOVA with 2x2 factors using the alpha of 0.05 in order to show the relationships between gender, religious conviction and involvement in premarital sex, it also used the 2x3 CHI SQUARE method using the alpha of 0.05 to show the relationship between premarital sex involvement and religious conviction and at the same time the researchers used 2x2 CHI SQUARE method using the alpha of 0.05 to show as well the relationship of premarital sex involvement and gender. The researchers had 150 respondents for this study 75 of which were males and 75 were females. The respondents for this study 75 of which were males and 75 were females. The respondents were all college students of different colleges of Tacloban City regardless of their year level, course and age. The study was conducted in Tacloban City particularly in STI College Tacloban, AMA Computer Learning Center (ACLC), Eastern Visayas State University (EVSU), Leyte Colleges and ABE Tacloban College. The result of the study indicated that only 46% of college students were involved in premarital sex. Although those who did not engage PMS, they still engage in sexual behaviors such as holding hands, kissing, necking and petting. In the ANOVA computation, the F values, obtained from F Table, shows us that there was no significant difference between premarital sex involvement and religious conviction because using the alpha of 0.05, in the F table with the degrees of freedom of 1, 60, the F obs for column which is 1.54 does not exceed the F value of 4.00. Therefore, we accept H0 wherein religious conviction alone does not matter with premarital sex involvement. However, there is a significant difference between two sexes (males and females) in their involvement in premarital sex because using alpha 0.05, with a degree of freedom 1, 60, the F obs 6.23 exceeds the F value 4.00. Therefore, we reject H0 because there was a significant difference between the two sexes and premarital sex involvement. When we look at the interaction the two sexes, premarital sex involvement and religious conviction using the alpha 0.05, with a degree of freedom of 1, 60, the F obs 4.95 exceeds the F value of 4.00. Therefore, we reject H0, because there is an interaction effect between the two sexes and involvement in premarital sex and religious conviction. It was also found out that males were more likely to engage in premarital sex than females because majority of the male respondents were involved in premarital sex. It was found out based on the study that love is the major reason for the involvement of the two sexes in premarital sex and that it is because of the personal choice of both sexes that influence them to engage in premarital sex. And giving them a change time and events, both sexes (male and female) wish that they have not engage in premarital sex. Males were found out that they were not guilty with their involvement in premarital sex while females were found to be guilty of their involvement in premarital sex.
Undergraduate thesis (BASS Psychology) -- University of the Philippines, Tacloban.